Micropropagation and acclimatization of Musa Acuminata cv. Mas and Raja Udang / Syed Abdullah Syed Mustaffa - Syed Mustaffa, Syed Abdullah (Faculty of Plantation and Agrotechnology, 2019)
Tissue culture method is the best method to overcome the shortage of planting material. The plantlets produced by tissue culture method are identical to the parent plant. This research was aimed to produce high quality planting materials of Musa Acuminata cv. Mas and Raja Udang. It was also intended to compare the regeneration efficiency of the two cultivars studied. Murashige and Skoog media added with BAP and NAA hormones were prepared and used for micropropagation of the bananas. The banana suckers were collected and surface-sterilized with ethanol and sodium hypochlorite solution. Then, the explants were cultured on MS medium. The explants were cultured under different growth conditions (light or dark conditions) to investigate the effect of light on the regeneration efficiency of the explants. Evaluation was performed to compare the shoot regeneration efficiency of Musa acuminata cv. Mas and Raja Udang in tissue culture. The plantlets were transferred to the potting mix consisting of topsoil, sand and farm yard manure in the ratio of 1:1:1. Acclimatization of plantlets was carried out before field planting purpose.